Banking Soundness and Monetary Policy. (International Monetary Fund, 1997)
Banking sector problems have affected many IMF member countries, and measures to remedy these problems as well as to prevent their recurrence deeply concern central bankers and policymakers. the papers and comments published in this volume and edited by Charles Enoch and John H. Green were presented at the Seventh Seminar on Central Banking sponsored by the IMF. The topics discussed include banking soundness and the macroeconomy, prudential standards, the role of the central bank during problems of banking soundness, and bank restructuring.